Higher Dementia Risk in People With Gastroesophageal Reflux Disease: A Real-World Evidence - Gau, Shuo-Yan; Lai, Jung-Nien; Yip, Hei-Tung; Wu, Meng-Che; Wei, James Cheng-Chung (Frontiers in Aging Neuroscience, 2022)
Background: Whether or not patients with gastroesophageal reflux disease (GERD) have a higher risk of developing subsequent dementia remains unknown, and no observational evidence from population-based data is available. This study was to determine whether patients with GERD have a higher future risk of developing dementia. Methods: For the period 2000-2012, datasets from the Longitudinal Health Insurance Database (LHID, subset of National Health Insurance Research Database in Taiwan) were analyzed. Definition of GERD was based on ICD-9-CM codes 530.11 and 530.81 and prescriptions for PPIs. After matching gender, age, index year, and comorbidities, each GERD patient was matched with four control patients without GERD. Future risk of dementia was evaluated, and sensitivity analysis of subgroups was conducted to clarify the potential association. Results: In the present study, 13,570 patients were included in the GERD cohort and 54,280 patients were included in the control cohort. Patients with GERD showed higher risk developing dementia than control group, with an aHR of 1.34 (95% C.I., 1.07, 1.67). In GERD patients between above 70 years old, the risk of developing dementia was higher than that of the control groups (aHR= 1.34; 95% C.I., 1.01, 1.77). Conclusions: Patients with GERD showed higher incidence of dementia, and elder patients had the highest risk of developing dementia. Clinicians should be concern of the association between GERD and dementia and should develop strategies to prevent dementia while managing patients with GERD. Keywords: gastroesophageal reflux disease; dementia; NHIRD; cohort study